Ekonomi Syariah dan Hukum: Harmonisasi Prinsip dan Praktik - Kolbiah, Fitri Durotul; Haryati, Dini; Herliani, Pakinah; Gusvita, Maisarah; Ardiansyah, Muhamad; Nizom, Asrul; Ramadhoni, Dika (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity took the form of a seminar entitled sharia economics and law: harmonizing principles and practices, with the aim of increasing public and academic understanding of the relationship between Sharia economic principles and positive legal aspects in Indonesia. This activity was motivated by the limited public literacy regarding the implementation of Sharia economics in accordance with legal regulations. The implementation method included lectures, interactive discussions, and a question-and-answer session. The results showed an increase in participants' understanding of the basic concepts of Sharia economics, its legal basis, and the challenges of harmonizing Sharia principles and practices in the field. This activity is expected to strengthen legal awareness and encourage the just and sustainable implementation of Sharia economics.